Arc of Justice: A Saga of Race, Civil Rights, and Murder in the Jazz Age - Jones, Rheti S. (Labour / Le Travail, 2006)
The article reviews the book, "Arc of Justice: A Saga of Race, Civil Rights, and Murder in the Jazz Age," by Kevin Boyle.
Keywords: ARC of Justice: A Saga of Race; Civil Rights & Murder in the Jazz Age (Book); BOOKS – Reviews; BOYLE; Kevin; Civil rights; Nonfiction